(3JhGRf GdeUGdM ai YbO GdHjY GdOhdi ddHVGFY habG dGJaGbjI ajjfG dYGe (B1980 / s - (3haGA eUWai eMeO YKeGfs; (3SejMI GdbdjhHi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2005)
(3GdJhGRf gh GdSeI GdLhgQjI GdJi NdbgG Gddg ai LejY GdXhGgQ GdchfjI (B: (3hGdJi JYHQ Yf GdUhQI GdMbjbjI ddYOGdI hGdeSGhGI Hjf GdeNdhbGJs
(3jTJed Ydi edGMb(B: (3UaMGJ (B263-285s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2005s
(3HHdjhLQGajG(B: (3UaMGJ (B287-305s
Keywords: (3GdbGfhf GdJLGQjs; (3GJaGbjI ajjfGs; (3JhGRf GdeUGdMs; (3YbO GdHjY GdOhdis; (3eQMdI GdeaGhVGJs; (3TQhW GdGjLGHs; (3GdbHhd GdeJGNQs; (3SMH GdbHhds; (3UhQ GdbHhds; (3GdSchJs; (3eaghe GdJWGHbs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs